Numerical simulation of the proximal convergence region of a regurgitant orifice - Myers, Jerry G.; Green, Derek W.; Anayiotos, Andreas (My University, 1993)
The quantification of vascular regurgitation has recently focused on a new method, the method of Proximal Isovelocity Surface Area (PISA). Based on the continuity equation, the flow through a regurgitant orifice may be calculated by determining the flow through a proximal isovelocity surface area. The flow in the neighbourhood of an orifice is composed of a series of equivelocity contours which converge in a uniform radial manner into the orifice. Investigators have used this technique by assuming a PISA surface (hemispherical, hemielliptical etc.) and multiplying by the corresponding aliasing velocity which is easily obtainable with color Doppler. None of the methods used so far directly obtained the contour shape. Instead, these techniques verified the accuracy of the assumed contour in the flow calculation by comparison with the orifice flow rate. A theoretical method that directly obtains the isovelocity contours in a circular orifice model of two different diameters is presented here. Such calculations will provide new information about the shape of the contour and the optimum measurement distance from the orifice. This method could be expanded to provide information on how to determine the isovelocity contours for non-circular orifices. Additionally, the theoretical model could help investigators expand on a corrected PISA Model to account for surrounding leaflet geometry surface motion and the non-Newtonian character of blood.
Keywords: Biomechanics; Hemodynamics; Mathematical models; Holes